Dynamic Modeling and Simulation of a PEM Fuel Cell (PEMFC) during an Automotive Vehicle’s Driving Cycle - Biberci, M. A.; Celik, M. B. (Engineering, Technology & Applied Science Research, 2020)
Polymer Electrolyte Membrane Fuel Cells (PEMFCs) are the most appropriate type of fuel cells for application in vehicles due to their low operational temperature and high-power density. In this paper, a zero-dimensional, steady state thermodynamic modeling for an automotive 90kW PEMFC system has been built up in order to investigate the effects of operating parameters such as vehicle acceleration and operating pressure on the size of the system elements, heat and water system constitution, fuel consumption, and efficiency. A dynamic model was formed for the fuel cell power system in MATLAB. Power output and power losses of the system were investigated at 3atm operation pressures.